Parkinson mice show functional and molecular changes in the gut long before motoric disease onset - Gries, Manuela; Christmann, Anne; Schulte, Steven; Weyland, Maximilian; Rommel, Stephanie; Martin, Monika; Baller, Marko; Röth, Ralph; Mellein, Stefanie; Unger, Marcus; Liu, Yang; Sommer, Frederik; et al. (Molecular neurodegeneration, 2021)
There is increasing evidence that Parkinson’s disease (PD) might start in the gut, thus involving and compromising also the enteric nervous system (ENS). At the clinical onset of the disease the majority of dopaminergic neurons in the midbrain is already destroyed, so that the lack of early biomarkers for the disease represents a major challenge for developing timely treatment interventions. Here, we use a transgenic A30P-α-synuclein-overexpressing PD mouse model to identify appropriate candidate markers in the gut before hallmark symptoms begin to manifest.
Gesehen am 18.08.2021